2021
DOI: 10.1039/d1tb00249j
|View full text |Cite
|
Sign up to set email alerts
|

Electronic control of drug release from gauze or cellulose acetate fibres for dermal applications

Abstract: Electronic controlled drug release from fibres was studied using ibuprofen as a model drug, one of the most popular analgesics, to impregnate gauze and cellulose acetate (CA) membranes. Conductivity in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The coating of hydrophobic sponge with a conducting polymer can convert its surface to hydrophilic one, and the contact angle could be varied (Stejskal et al 2008). The electroactivity of conducting polymers could be exploited in the control of adsorption processes by applying electrical potential (Baptista et al 2021;Xu et al 2021). In extended studies, polypyrrole can be replaced with polyaniline or polymers of ringsubstituted aniline derivatives, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The coating of hydrophobic sponge with a conducting polymer can convert its surface to hydrophilic one, and the contact angle could be varied (Stejskal et al 2008). The electroactivity of conducting polymers could be exploited in the control of adsorption processes by applying electrical potential (Baptista et al 2021;Xu et al 2021). In extended studies, polypyrrole can be replaced with polyaniline or polymers of ringsubstituted aniline derivatives, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although a similar behaviour was observed for all systems concerning the voltage values that lead to the highest drug retention, the voltage that maximised the IBU release ranged between +0.3 V, +0.5 V, and +0.8 V for the various systems. This inconsistency in values can be attributed to the possible bending of the systems during immersion in SBF, which can affect the distance between the electrodes [22].…”
Section: Drug Release Testsmentioning
confidence: 99%
“…The authors demonstrated that the relationship between the applied current, the content encapsulated in the fibrous layer of PPy, and the amount of drug released (dexamethasone, indomethacin, and aspirin) is linear. In 2021, Baptista et al [22] studied the electronically controlled release of ibuprofen (IBU) previously impregnated in gauze and CA membranes. They obtained a conductivity range of 1-10 mS/cm in gauze functionalised with PPy and CA fibres, providing a controlled drug release by electrical stimuli in a system composed of PPy/IBU/PPy membranes and a silver electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Polypyrrole (Figure 1a) is of special interest for this type of applications because, in the contrast to polyaniline, it does not lose the conductivity under neutral and physiological conditions, and this applies especially to polypyrrole nanotubes 5–7 . This is important both for the environmental issues, such as water‐pollution treatment, 3 in biomedicine, 8 and with respect to drug delivery 9–11 . In addition to the dye‐adsorption ability of polypyrrole, its conductivity and electroactivity might become exploited in the control of adsorption by applying electric potential.…”
Section: Introductionmentioning
confidence: 99%
“…This makes conducting polymers a special potential class of electrically driven adsorbents. For example, the dye adsorption can be affected in this way 12 and the same principle was exploited in the controlled drug delivery 9,11,13,14 or in electrooxidative 15 and electrocatalytic 16 removal of pollutant dyes.…”
Section: Introductionmentioning
confidence: 99%